Amperometric differential determination of ascorbic acid in beverages and vitamin C tablets using a flow cell containing an array of gold microelectrodes modified with palladium - Matos, R. C.; Augelli, M. A.; Pedrotti, J. J.; Lago, C. L.; Angnes, L. (Wiley-Blackwell, 1998)
A simple and attractive method for quantification of ascorbic acid (AA) in beers, soda, natural juices and commercial vitamin C tablets was achieved by combining Bow injection analysis and amperometric detection. An array of gold microelectrodes electrochemically modified by deposition of palladium was employed as working electrode which was almost unaffected by fouling effects. Ascorbic acid was quantified in beverages and vitamin tablets using amperometric differential measurements. This method is based on three steps involving the flow injection of: 1) the sample plus a standard addition of AA, 2) the pure sample, and 3) the enzymatically-treated sample. The enzymatic treatment was carried out with Cucumis sativus tissue, which is a rich source of ascorbate oxidase, at pH 7. The calibration plots for freshly prepared ascorbic acid standards were very linear in the concentration range of 0.18-1.8 mg L-1 with a relative standard deviation (RSD) < 1%, while for real samples the deviations were between 2.7% to 8.9%.
Keywords: ascorbic acid; flow injection analysis; beverages; vitamin C; modified microelectrodes